Preparation method for obtaining nano structure with micro-nano morphology through nano treatment of pure titanium surface and application thereof
By using a neutral organic electrolyte on the surface of pure titanium implants, a nanopore structure with both micro-nanomorphology was prepared, which solved the problem of insufficient mechanical strength of nanostructures in the prior art, and realized the The effect of retaining micron morphology and enhancing biological activity is achieved on the surface of the implant.
Patent Information
- Application Number
- CN202411603674.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The prior art is difficult to prepare nanostructures with micro-nanomorphism on the surface of pure titanium implants, while retaining the original microstructures, and the mechanical strength of the prepared nanostructures is not sufficient to meet the dental/intra-bone implants. need.
Using neutral electrochemical anodizing method based on organic electrolyte, the conductivity and pH of the electrolyte are adjusted while preparing nanopores on the pure titanium surface, and using a DC voltage of 40-80V, a better mechanical strength is prepared. nanopore structure with micro-nanomorphology.
It realizes the preparation of nanopores on pure titanium surfaces with different morphology while retaining micron-level morphology, which improves the hydrophilicity and protein adhesion ability of the surface, and has better mechanical properties, which are suitable for dental/intra-bone implantation. body.
Smart Images

Figure CN119145020A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical fields of nano-engineering, nano-processed pure titanium implants, micro-nano preparation, and micro-nano morphology, and relates to a preparation method and application of a nano-processed pure titanium surface to obtain a nanostructure with both micro-nano morphology, and specifically to a preparation method and application of a nano-processed pure titanium implant surface to obtain a nanostructure with both micro-nano morphology. Background Art
[0002] Pure titanium is a widely used dental / bone implant material. Its biological activity is affected by surface morphology, chemistry and hydrophilicity. In order to improve its surface activity and promote the regeneration and combination of soft and hard tissues on its surface, physical and chemical methods such as micron-level roughening, hydrophilic modification, and ion implantation are gradually applied to the surface of pure titanium implants. [1] In recent years, nanotechnology has gradually been applied to the surface treatment of pure titanium implants to prepare structures with nano-level morphology on their surfaces to further enhance cell activity and regulate their functions.
[0003] Among many nanotechnologies, electrochemical anodization (EA) has the advantages of simple operation, high efficiency, and can be extended to a variety of metal surfaces. EA can prepare pore-like nanostructures on the surface of anode titanium. [2] In simple terms, EA is to immerse the anode and cathode metals in an electrolyte containing F ions at the same time, and through a stable DC supply, the anode metal surface is oxidized and synthesized into soluble Ti-F compounds, which are dissolved in the electrolyte, thereby etching out pore-like nanostructures such as nanopores or nanotubes. [3] .
[0004] This pore-like nanostructure not only increases the surface roughness, but also provides more surface area, which helps to increase cell attachment points and promote cell proliferation and differentiation. In addition, these nanostructures can also serve as drug delivery systems to further promote tissue regeneration by slowly releasing growth factors or other bioactive molecules.
[0005] Nano-treatment of pure titanium by EA can be completed in an organic electrolyte or a water-based electrolyte containing F ions, and the electrolyte can be either an acidic or neutral electrolyte. However, most acidic or water-based electrolytes are highly corrosive and conductive, and usually dissolve the surface morphology of pure titanium during the EA process, preparing clustered, relatively independent nanotubes, which in turn destroy the original micron-scale morphology of the pure titanium implant surface. However, establishing a neutral, organic electrolyte and adjusting the EA parameters may make it possible to prepare a nanopore structure on the surface of pure titanium, which is expected to retain its original micron morphology to a certain extent while preparing the nano-morphology. In addition, previous reports have shown that the elastic modulus of relatively independent nanotubes prepared by EA is only 0.3-16.6 GPa. [4] The gaps between the nanopores are filled with the Ti-OF composite generated by EA, so it may have higher mechanical strength and is more suitable for preparation as the surface of pure titanium implants and their accessories. [5, 6] . Although some studies have found that surface-fused nanopores can be prepared on the surface of pure titanium by EA, there is no clear method that can be widely applied to different pure titanium surfaces and retain the original micron morphology of the pure titanium surface while preparing nanopores, and finally obtain an EA system with both micro-nanomorphology and nanostructure on the pure titanium surface. In addition, pure titanium is the most widely used material for preparing dental / endobone implants and their accessories, and the nanopores formed on its surface need to have certain mechanical strength, hydrophilicity and protein adhesion ability to ensure its mechanical stability and biological activity.
[0006] Therefore, there is an urgent need to design an EA system that can be widely used on pure titanium surfaces of different morphologies, so that it can retain its original microstructure while preparing nanostructures, and prepare nanostructures with better mechanical strength than nanotubes, and explore its surface mechanical strength, hydrophilicity and protein adhesion ability. Summary of the invention
[0007] In order to address the deficiencies in the prior art, the present invention aims to provide a neutral, organic electrolyte-based EA system that can be applied to pure titanium surfaces with different morphologies to prepare nanopores while retaining their original micron-level morphology, thereby preparing a nanopore structure with both micro-nano morphology, which is particularly suitable for the surfaces of pure titanium implants and their accessories.
[0008] Electrochemical anodization is a promising nanotechnology that opens up new possibilities for improving the bioactivity of implants and promoting rapid and effective bone integration by creating nanoscale structures on the surface of pure titanium implants. With in-depth research and application optimization of this technology, it is expected that the clinical performance of titanium implants will be significantly improved in the future.
[0009] The main technical difficulties and challenges overcome by the present invention include: how to provide an EA system that can be widely used for pure titanium surfaces with different morphologies, and retain the original micron morphology of the pure titanium surface while preparing nanopores; the system has a certain ductility, and can be realized on pure titanium surfaces with different morphologies between 40-80V voltage to obtain the preparation of nanostructures with both micro-nano morphology; the nanopores with both micro-nano morphology prepared by the present invention have better mechanical strength than nanotubes, and are suitable for use in the surface of intrabone implants; in addition, compared with the pure titanium surface, the nanopore surface with both micro-nano morphology prepared by the present invention has better hydrophilicity and protein adhesion ability, can be quickly wetted by plasma after implantation into the human body, is conducive to the adhesion of tissue proteins and cells, and also has a certain drug loading function.
[0010] The present invention provides an EA system and method, which can prepare nanopores with certain stability and protein adhesion ability on pure titanium surfaces with different morphologies, and while preparing the nanopores, the micron morphology of the pure titanium surface is retained as much as possible, and finally the surface characteristics of the pure titanium surface with both micro-nano morphology and nanostructure are obtained.
[0011] The present invention provides a preparation method for nano-treating the surface of pure titanium to obtain a nanostructure with both micro-nano morphology, and the specific steps of the preparation method are as follows: The first step is to stir 0.5-10% by volume of deionized water and 0.2-0.5% by mass of ammonium fluoride in an organic solvent, ethylene glycol, to prepare an electrolyte; In the second step, before preparing nanopores on the pure titanium surface, the electrolyte obtained in the first step is pre-adjusted: pure titanium (pure titanium sheet, pure titanium rod, etc.) is EA'd by repeated electrochemical anodization to adjust the conductivity, pH and other parameters of the electrolyte; The third step is to adjust the conductivity of the electrolyte to 480-495 μs / cm by adjusting the electrolyte in the second step. 2 , the pH is adjusted between 7.0 and 7.8 to achieve the optimal conditions for nanopore preparation (refer to the literature published by the inventors [3, 5]); In the fourth step, in the electrolyte obtained in the third step to achieve the optimal conditions for nanopore preparation, a voltage of 40-80V is provided by a DC regulated power supply to perform EA on pure titanium, which can prepare nanopore structures with a certain porosity and relatively uniform diameter on the surfaces of pure titanium with different roughness and morphology, while retaining its original micron-level morphology, and finally prepare a nanostructure with both micro-nano morphology on the surface of pure titanium.
[0012] In the first step, the volume fraction of the deionized water is 0.5-10%, preferably 1-3%.
[0013] In the first step, the mass fraction of ammonium fluoride is 0.2-0.5%, preferably 0.3%.
[0014] In the first step, the quality of the ethylene glycol is spectrally pure.
[0015] In the first step, the stirring speed is 300-1000 rpm, preferably, 350-500 rpm.
[0016] In the first step, the stirring time is 30-60 minutes, preferably 40-45 minutes.
[0017] In the second step, the pure titanium is commercially available pure titanium, such as one or more of TA1, TA2, etc., preferably TA2.
[0018] In the second step, the morphology of the pure titanium includes smooth titanium, rough titanium, micro-groove titanium, etc.
[0019] In the second step, the pure titanium includes pure titanium sheets, pure titanium rods, etc. The thickness of the pure titanium sheets is 0.2-0.5 mm, preferably 0.25-0.3 mm, and the diameter of the pure titanium rods is 1 mm-10 mm, preferably 1 mm-5 mm.
[0020] In the second step, the number of EA is 2-8 times, preferably 3-5 times.
[0021] Before the second step, it also includes building an EA electrochemical treatment system: pour the electrolyte obtained in the first step into a 500ml beaker, cover the beaker with a foam sponge, immerse the pure titanium of the cathode and anode through the foam sponge into the electrolyte, and connect the power supply to the anode titanium and the cathode pure titanium respectively for EA. The EA process needs to be completed on a magnetic stirrer, and the speed is adjusted to 200-1000 rpm. The electrolyte needs to be stirred continuously during the process; preferably, the pure titanium of the cathode and the anode is consistent or similar (if the anode is a pure titanium sheet, the anode should also be a pure titanium sheet of similar thickness), and the speed is adjusted to 300-500 rpm.
[0022] In the second step, the pre-adjusted EA parameters are: 80V, maximum current 50mA, 2 hours per time, and a total of 2-10 times of adjustment; preferably, the number of adjustments is 4-6 times.
[0023] In the third step, the conductivity of the electrolyte is adjusted to 480-495 μs / cm 2 , preferably, 483~492μs / cm 2 .
[0024] In the third step, the pH is adjusted between 7.0 and 7.8, preferably, between 7.2 and 7.6.
[0025] In the fourth step, the DC regulated power supply provides a voltage of 40-80V, preferably 60-80V.
[0026] In the fourth step, the EA time is 5-30 minutes, preferably 10 minutes.
[0027] The present invention also provides a titanium product prepared by the preparation method as described above, wherein the nanopores on the surface of the titanium product have a pore size of 40-60 nm, a porosity of 10%-15%, and a stable surface of the nanopores with substantially no cracks.
[0028] The present invention also provides a pure titanium nanoprocessing system, the system comprising: DC regulated power supply: maximum voltage must be ≥80V, maximum current must be ≥50mA; Closed electrolytic cell: The outer shell should be made of inert materials such as plastic or glass, and the top should be able to be closed, for example: a plastic beaker, the top is closed by a plastic cover or foam plastic.
[0029] Neutral electrolyte: needs to be prepared using ethylene glycol, deionized water and ammonium fluoride.
[0030] The present invention also provides the use of the preparation method as described above, the titanium product as described above, or the system as described above in the surface treatment of pure titanium biomaterials.
[0031] Specifically, the pure titanium biomaterial includes intraosseous implants, dental implants, upper bases, and the like.
[0032] In the specific embodiment of the present invention, the SEM (scanning electron microscope) and AFM (atomic force microscope) data illustrate that the present invention is applicable to pure titanium surfaces of different morphologies, including but not limited to polished smooth titanium, micro-grooved titanium polished in a single direction, and rough titanium with irregular surface morphology. The SEM and AFM images also reflect that when the present invention prepares nanopores on the pure titanium surfaces of different materials, the original micron morphology of the pure titanium material will be retained to a certain extent, and finally a surface with both micro-nano morphology will be achieved. XPS (X-ray photoelectron spectroscopy) and XRD (X-ray diffraction) data explain that when the present invention performs EA treatment on the pure titanium surface, the F element in the electrolyte will be introduced into the prepared nanopore surface, but the lattice of the pure titanium surface will not be changed. The WCA (water contact angle) data suggests that the present invention will greatly improve its hydrophilicity while preparing nanopores with both micro-nano morphology on the pure titanium surface. The protein adhesion experiment explains that the nanopores with both micro-nano morphology prepared on the pure titanium surface by the present invention can enhance the adhesion of different proteins on its surface, indicating that it has good biological activity. In addition, nanoindentation experimental data show that nanopores with both micro-nano morphology prepared on pure titanium surfaces with different morphologies have a Young's modulus of about 30-60 GPa and a hardness of 1.5-2.7 GPa, which are qualified to become dental / bone implants.
[0033] The present invention can retain the micron morphology of the original implant surface during the process of preparing nanopores with both micro-nano morphology on the pure titanium surface, and finally obtain a nanopore structure with both micro-nano morphology on the pure titanium surface.
[0034] Compared with the prior art, the beneficial technical effects of the present invention are as follows: the main advantage of the present invention is that it can be applied to pure titanium surfaces of different morphologies, and while preparing nanopores on the pure titanium surface, retains its original micron-level morphology, and finally prepares a nanostructure with both micro-nano morphology on the pure titanium surface; the nanopore structure with both micro-nano morphology prepared on the pure titanium surface of the present invention is a nanotube structure fused on the surface, and compared with simple nanotubes, the nanopores have better mechanical strength and stability (compared to the advantages of nanotubes); the nanopore structure with both micro-nano morphology prepared on the pure titanium surface of the present invention can significantly improve the hydrophilicity and protein adhesion ability of the pure titanium surface, providing a basis for its further clinical transformation on the implant surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0036] Figure 1 This is a schematic diagram of the preparation method of the present invention for nano-treating the surface of pure titanium to obtain a nanostructure with both micro-nano morphology.
[0037] Figure 2 The scanning electron microscope (SEM) images show that the electrochemical oxidation treatment (EA) system of the present invention is used to prepare nanopores with both micro-nano morphology on pure titanium surfaces with different morphologies.
[0038] Figure 3 The atomic force microscope (AFM) images show the characteristics of pure titanium and the nanopores with micro-nano morphology prepared on the surface of pure titanium by the present invention: (A) Smooth titanium has a smooth surface, and the nanopores S80 (D) (smooth nanopores) prepared on its surface have micron-scale morphology but are relatively smooth, while the nanoscale morphology is relatively rough; (B) Rough titanium has a micron-scale rough surface, and the nanopores R80 (E) (rough nanopores) prepared on its surface retain their original micron-scale morphology and are nanopores with micro-nano morphology; (C) Micro-grooved titanium has a micron-scale morphology, i.e., micro-grooves, and the morphology of the nanopores M60 (F) (micro-grooved nanopores) prepared on its surface is based on its original micro-grooved surface, retaining its original micron-scale morphology.
[0039] Figure 4 X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD) diagrams indicate the chemical differences between pure titanium and the nanopores with micro-nano morphology prepared on the surface of pure titanium according to the present invention: the left figure is an XPS diagram, and the right figure is an XRD diagram.
[0040] Figure 5 The water contact angle (WCA) experiment suggests that the nanoporous structures with micro-nano morphology prepared on different pure titanium surfaces in the present invention have better hydrophilicity.
[0041] Figure 6 The protein adhesion experiment suggests that compared with pure titanium, all the nanoporous structures with micro-nano morphology prepared on different pure titanium surfaces of the present invention can adhere to more proteins.
[0042] Figure 7 Nanoindentation experiments show that the nanoporous structure with micro-nano morphology obtained by nano-treating the surface of pure titanium by the preparation method of the present invention has a Young's modulus of about 30-60 GPa and a hardness of 1.5-2.7 GPa, compared with the reported titanium nanotubes with a Young's modulus of only 0.3-16.6 GPa and a hardness of 100-300 N / mm 2 (Hardness of 0.1-0.3GPa) [4, 7] , the nanopore structure has better mechanical properties. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0044] The present invention is further described in detail in conjunction with the following specific examples and drawings, and the protection content of the present invention is not limited to the following examples. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are included in the present invention, and the attached claims are the scope of protection. The process, conditions, reagents, experimental methods, etc. for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art, and the present invention does not specifically limit the content.
[0045] The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] In all examples shown and discussed herein, any specific values should be interpreted as merely exemplary and not as limiting. Therefore, other examples of the exemplary embodiments may have different values.
[0047] The present invention discloses a preparation method and application of nano-treating a pure titanium surface to obtain a nanostructure with both micro-nano morphology. The preparation method is suitable for nano-treating pure titanium surfaces with various morphologies, and can prepare nanopores on pure titanium surfaces with different morphologies while retaining the original micron morphology as much as possible, thereby realizing the preparation of nanopores with both micro-nano morphology on the pure titanium surface. In addition, the nanopores with both micro-nano morphology prepared on the pure titanium surface by the preparation method have excellent hydrophilicity and protein adhesion properties, and have better mechanical properties than traditional nanotubes, and have the potential to be applied to the surface treatment of pure titanium implants and bases. The present invention has broad application prospects.
[0048] Unless otherwise specified, the test materials used in the examples of the present invention are all conventional biochemical reagents. Example
[0049] Experimental Materials: Reagents: ethylene glycol (spectrally pure), deionized water, ammonium fluoride (super pure).
[0050] Equipment: DC regulated power supply with voltage range greater than or equal to 80V and maximum current greater than or equal to 50mA, for example: Keysight E36106B, analytical balance, magnetic stirrer.
[0051] Equipment: measuring cylinder, magnetic rotor, plastic beaker, magnetic stirrer (maximum speed greater than or equal to 1000rpm), sponge material, parafilm sealing film, and several pure titanium sheets.
[0052] Experimental methods: The preparation method of the present invention for nano-treating the pure titanium surface to obtain a nanostructure with both micro-nano morphology is as follows Figure 1 As shown, the specific steps are as follows: 1. Preparation of electrolyte: Under the precise guidance of the analytical balance cylinder, prepare an ethylene glycol electrolyte containing 1% volume fraction of deionized water and 0.3% mass fraction of ammonium fluoride. For example, accurately weigh 1.5g of ammonium fluoride powder and 5ml of deionized water, and pour them into 495ml of ethylene glycol solution. Add clean tiles to the solution and stir for 30-60 minutes under the action of a magnetic stirrer to fully dissolve the ammonium fluoride powder and stir evenly.
[0053] 2. Preparation of pure titanium: Rough titanium is a commercially available pure titanium sheet, which is slightly polished with 200-grit sandpaper, with a thickness of 0.25mm. The length and width can be cut into appropriate sizes with scissors, such as 10mm*10mm; micro-grooved titanium is a rough titanium that is polished in a single direction using 500, 1000, and 1500-grit sandpaper in sequence; smooth titanium is a rough titanium that is repeatedly polished in multiple directions using 500, 1000, 1500, 2000, 3000, and 5000-grit sandpaper, and then polished with polishing paste + polishing cloth. The prepared titanium sheet is repeatedly rinsed with deionized water + anhydrous ethanol, immersed in anhydrous ethanol for ultrasonic washing, and air-dried.
[0054] 3. Build an EA electrochemical treatment system: Pour the electrolyte obtained in step 1 into a 500ml beaker and cover the beaker with a foam sponge. Place the cathode and anode pure titanium sheets through the foam sponge and immerse them in the electrolyte. Connect the power supply to the anode titanium and cathode titanium respectively for EA. The EA process needs to be completed on a magnetic stirrer with a speed of 350-500 rpm. The electrolyte needs to be stirred continuously during the process.
[0055] 4. Electrolyte pre-conditioning: This part refers to the previously published articles [3, 5]. Through repeated EA of pure titanium (including rough titanium, micro-grooved titanium and smooth titanium, with no limit on surface roughness), the EA parameters were adjusted to: 80V, maximum current 50mA, 2 hours per time, and a total of 5-10 times, so that the conductivity of the electrolyte obtained in step 1 was 480~495μs / cm 2, pH is adjusted between 7.0 and 7.8. The pre-adjustment of the electrolyte obtained in step 1 of this embodiment is consistent with the electrochemical system used in the formal EA process.
[0056] 5. EA process: Apply the electrolyte pre-adjusted in step 4, adjust the EA parameters to: voltage 40, 60 or 80V, maximum current 30-40mA, each EA preparation time for nanopores is 10 minutes, and EA is performed on pure titanium (rough titanium, micro-grooved titanium and smooth titanium). Nanopore structures with a certain porosity and relatively uniform diameter and micro-nano morphology can be prepared on the surface of pure titanium with different roughness and morphology, namely, each group of nanopores S80, M60, R80.
[0057] The groups of nanopores S80, M60, and R80 obtained by the above method were respectively measured by SEM, AFM, XPS, XRD, water contact angle experiment WCA (experimental instrument: OCA Pro15 Dataphysics; liquid: deionized water; amount of liquid added each time: 2 μL; taking a photo 1 second after adding to measure the contact angle), protein adhesion experiment, and nanoindentation experiment (experimental equipment: Agilent-G200; indenter: Berkovich triangular indenter, angle of 142.3°; pressure direction: perpendicular to the sample surface, maximum pressure of 10000 μN) to measure the groups of nanopores S80, M60, and R80 obtained in the embodiment of the present invention, thereby characterizing the nanopores prepared on the pure titanium surface in the embodiment of the present invention.
[0058] The nanopores (groups of nanopores S80, M60, and R80) prepared on the pure titanium surface in the present invention and their characterizations are as follows: like Figure 2As shown, under the EA system of the present invention, it is suggested that: compared with pure titanium, the embodiment of the present invention uses 40V, 60V and 80V to oxidize the surface of the smooth titanium (STi), micro-grooved titanium (MTi) and rough titanium (RTi) surface to obtain the nanopore structure of the anode pure titanium surface for 10 minutes. The present invention finds that a surface-fused nanopore structure can be prepared on the surface of three pure titanium surfaces with different morphologies, and while preparing the nanopores, the original micron-level morphology can be retained, and finally a nanopore structure with both micro-nano morphology is achieved. Smooth titanium: has a smooth morphology, and the nanopores prepared on its surface have a nano morphology; micro-grooved titanium: there are parallel micro-grooves on the surface, and the nanopores prepared on its surface are arranged regularly along the micro-grooves on its surface; rough titanium: the surface roughness is irregular, and the nanopores prepared on its surface will retain its original micron-level irregular roughness to a certain extent. In addition, according to SEM analysis, the diameters of the nanopores (S80, R80) prepared on the surface of smooth titanium and rough titanium at 80V in the embodiment of the present invention are similar to the diameter of the nanopores prepared on the surface of micro-groove titanium at 60V (M60), so S80, R80 and M60 were selected for analysis and comparison in subsequent experiments.
[0059] like Figure 3 As shown, smooth titanium (A) has a smooth surface, and the nanopore S80 (D) (smooth nanopore) prepared on its surface has a nano-morphology surface; rough titanium (B) has a micron-level rough surface, and the nanopore R80 (E) (rough nanopore) prepared on its surface retains its original micron morphology and is a nanopore with both micro-nano morphology; micro-grooved titanium (C) has a micron-level morphology, namely micro-grooves, and the morphology of the nanopore M60 (F) (micro-grooved nanopore) prepared on its surface is based on its original micro-grooved surface, retaining its original micro-morphology.
[0060] like Figure 4 As shown, the left figure is an XPS figure: Compared with the pure titanium surface, the nanopores with both micro-nano morphology prepared on the pure titanium surface in the embodiment of the present invention have F element components, which indicates that the EA oxidation process introduces the F element in the electrolyte into the pure titanium surface, forming a layer of Ti-F / Ti-OF complex. In addition, the nanopores prepared on different pure titanium surfaces in the embodiment of the present invention (each group of nanopores S80, M60, R80) all have better hydrophilicity, can be wetted by plasma and tissue fluid faster in the human body, and have the potential to enhance tissue healing, indicating that the nanopores with both micro-nano morphology of EA implants have the potential to be used on implants and abutment surfaces. The right figure is an XRD figure, indicating that there is no obvious difference between the surface lattice of the nanopores with both micro-nano morphology prepared on the pure titanium surface in the embodiment of the present invention and the physical phase of the pure titanium surface.
[0061] like Figure 5As shown, the present invention uses the water contact angle test WCA to measure the hydrophilicity of the pure titanium surface and the pure titanium nanopores with micro-nano morphology obtained in the embodiments of the present invention (each group of nanopores S80, M60, R80), indicating that the hydrophilicity of the pure titanium surface without EA is general (water contact angle is 55.05±1.30°), while the hydrophilicity of all the pure titanium nanopore structures with micro-nano morphology is significantly better than that of the pure titanium surface (contact angle is 11.33~14.47°), and the difference is statistically significant. The WCA experiment of the present invention found that the nanopore structure with micro-nano morphology prepared by EA treatment of the pure titanium surface can significantly improve the hydrophilicity of the titanium sample surface, and is suitable for preparing materials that require strong hydrophilicity, especially medical bone / dental implant machine accessories.
[0062] like Figure 6 As shown, protein adhesion experiment (materials: pure titanium and various groups of nanopores S80, M60, R80) [8, 9] Tip: Compared with the pure titanium surface, all the nanopores (groups of nanopores S80, M60, and R80) prepared on the pure titanium surface in the embodiment of the present invention have better protein adhesion ability. The protein adhesion ability of the nanopores S80 and R80 on the pure titanium surface obtained by EA at 80V voltage in the embodiment of the present invention is higher than that of the nanopores M60 on the pure titanium surface obtained at 60V voltage. Including the most common albumin (BSA), mucoprotein, fibronectin and histone in plasma. The experiment suggests that the nano-treated pure titanium implant is conducive to the adhesion of protein components in plasma and tissue fluid on its surface, and helps cells to adhere to its surface. In addition, the increased protein adhesion amount also suggests that the nano-treated pure titanium implant, the nanopores with micro-nano morphology prepared on the pure titanium surface have the potential to be used as drug carriers to achieve local drug loading-controlled release and further enhance its biological activity in vivo.
[0063] Albumin is the most common protein in plasma, and its adhesion can assist other cells in colonizing and adhering to the surface of materials. Mucin is a common protein in saliva, and its adhesion can regulate cell adhesion and growth. Fibronectin is an important component of the extracellular matrix, and its adhesion is beneficial to promote the adhesion and secretion of extracellular matrix by fibroblasts. Histones are positively charged proteins, and their adhesion can simulate the loading of positively charged drug molecules on the surface of nano-treated implants to a certain extent.
[0064] like Figure 7As shown, the nanoindentation experiment (experimental equipment: Agilent-G200; indenter: Berkovich triangular indenter, angle of 142.3°; pressure direction: perpendicular to the sample surface, maximum pressure of 10000 μN) indicates that the nanoporous structure with micro-nano morphology prepared on the surface of the pure titanium material by nano-treatment in the embodiment of the present invention has a surface Young's modulus of about 30-60 GPa and a hardness of 1.5-2.7 GPa, compared with the Young's modulus of 0.3-16.6 GPa and the hardness of less than 1.0 GPa of the traditional nanotube. [4] , the nanopore structure has better mechanical properties.
[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
[0066] 1. T. Guo, K. Gulati, H. Arora, P. Han, B. Fournier, S. Ivanovski, Orchestrating soft tissue integration at the transmucosal region of titaniumimplants, Acta Biomater 124 (2021) 33-49. 2. K. Gulati, H.-J. Moon, T. Li, PT Sudheesh Kumar, S. Ivanovski, Titania nanopores with dual micro- / nano-topography for selective cellular bioactivity, Materials Science and Engineering: C 91 (2018) 624-630. 3. T. Guo, N.A.K. Oztug, P. Han, S. Ivanovski, K. Gulati, Old isGold: Electrolyte Aging Influences the Topography, Chemistry, and Bioactivityof Anodized TiO2 Nanopores, ACS Applied Materials & Interfaces 13(7) (2021)7897-7912. 4. S. Durdu, G. Cihan, E. Yalcin, A. Altinkok, Characterization andmechanical properties of TiO2 nanotubes formed on titanium by anodicoxidation, Ceramics International 47(8) (2021) 10972-10979. 5. T. Guo, S. Ivanovski, K. Gulati, Tuning electrolyte aging intitanium anodization to fabricate nano-engineered implants, Surface andCoatings Technology 447 (2022) 128819. 6. T. Guo, S. Ivanovski, K. Gulati, Fresh or aged: Short timeanodization of titanium to understand the influence of electrolyte aging ontitania nanopores, Journal of Materials Science & Technology 119 (2022) 245-256. 7. K. Oh, K. Lee, J. Choi, Influence of geometry and crystalstructures of TiO2 nanotubes on micro Vickers hardness, Materials Letters 192(2017) 137-141. 8. T. Guo, N.A.K. Oztug, P. Han, S. Ivanovski, K. Gulati, Untwiningthe topography-chemistry interdependence to optimize the bioactivity of nano-engineered titanium implants, Applied Surface Science 570 (2021) 151083. 9. T. Guo, N.A.K. Oztug, P. Han, S. Ivanovski, K. Gulati, Influenceof sterilization on the performance of anodized nanoporous titanium implants,Materials Science and Engineering: C 130 (2021) 112429.
Claims
1. A method for preparing a nanostructure with micro-nano morphology by nano-treating the surface of pure titanium, characterized in that: The preparation method The following steps are involved: The first step is to stir 0.5-10% by volume of deionized water and 0.2-0.5% by mass of ammonium fluoride in an organic solvent, ethylene glycol, to prepare an electrolyte; The second step is to pre-adjust the electrolyte obtained in the first step before preparing nanopores on the pure titanium surface: the pure titanium is EA-oxidized by repeated electrochemical anodization to adjust the conductivity and pH parameters of the electrolyte; The third step is to adjust the conductivity of the electrolyte to 480-495 μs / cm by adjusting the electrolyte in the second step. 2 , pH was adjusted between 7.0 and 7.8 to achieve the best conditions for nanopore preparation; In the fourth step, in the electrolyte obtained in the third step to achieve the optimal conditions for nanopore preparation, a voltage of 40-80V is provided by a DC regulated power supply to perform EA on pure titanium, which can prepare nanopore structures with a certain porosity and relatively uniform diameter on the surfaces of pure titanium with different roughness and morphology, while retaining its original micron-level morphology, and finally prepare a nanostructure with both micro-nano morphology on the surface of pure titanium.
2. The preparation method according to claim 1, characterized in that In the first step, The quality of the ethylene glycol is spectrally pure; and / or, The stirring speed is 300-1000 rpm; and / or, The stirring time is 30-60 minutes.
3. The preparation method according to claim 1, characterized in that: In the second step, The pure titanium is commercially available pure titanium; and / or, The morphology of the pure titanium includes smooth titanium, rough titanium, and micro-grooved titanium; and / or, The pure titanium may be in the form of a pure titanium sheet or a pure titanium rod; and / or, The number of EAs is 2-8 times.
4. The preparation method according to claim 1, characterized in that: Before the second step, it also includes building an EA electrochemical treatment system: pouring the electrolyte obtained in the first step into a 500ml beaker and covering the beaker with a foam sponge, immersing the pure titanium of the cathode and anode into the electrolyte through the foam sponge, and connecting the power supply to the pure titanium of the anode and cathode respectively for EA; the EA process needs to be completed on a magnetic stirrer, adjusting the speed to 200-1000 rpm, and the electrolyte needs to be continuously stirred during the process.
5. The preparation method according to claim 1, characterized in that: In the second step, The pre-adjusted EA parameters are: 80V, maximum current 50mA, 2 hours per time, and the number of adjustments is 2-10 times.
6. The preparation method according to claim 1, characterized in that: In the fourth step, the EA time is 5-30 minutes.
7. The titanium product prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The nanopores on the surface of the titanium product have a pore size of 40-60 nm and a porosity of 10%-15%, and the surface of the nanopores is stable with substantially no cracks.
8. A nano-processing system for pure titanium, using the preparation method according to any one of claims 1 to 6 to process the surface of pure titanium, characterized in that: The system comprises: DC regulated power supply: the maximum voltage of the power supply is ≥80V, and the maximum current is ≥50mA; Closed electrolytic cell: The shell of the electrolytic cell is made of inert material and its top is closed; Neutral electrolyte: The electrolyte is prepared with ethylene glycol, deionized water and ammonium fluoride.
9. Use of the preparation method according to any one of claims 1 to 6, or the titanium product according to claim 7, or the system according to claim 8 in the surface treatment of pure titanium biomaterials.
10. The use according to claim 9, characterized in that The pure titanium biomaterial comprises an intraosseous implant, a dental implant and an upper base.
Citation Information
Patent Citations
Titanium dioxide nanocomposite and one-step preparation method by utilizing anodic oxidation device
CN102534727A
Method of preparing double-wall TiO2 nanotube array with good photocatalytic performance through three-electrode technique
CN102817062A
Method for preparing transparent free-standing titanium dioxide nanotube array film
US20190241441A1
Method for preparing transparent independent titania nanotube array films
WO2018095290A1
Material having surface modified by super capacitance, preparation method therefor and application thereof
WO2019218754A1
Cited By
Nanopore titanium material, preparation method thereof and application of nanopore titanium material in preparation of implant titanium abutment
CN120330840A
Preparation method and application of medical implant
CN121023608A
